CSR IN BANKING SECTOR A LITERATURE REVIEW AND NEW RESEARCH DIRECTIONS - Tran, Yen Thi Hoang (ĐHKT, 2016)
Theoretical and empirical researches entirely addressed the issues of corporate social responsibility since 1950s. This paper aims at providing a review of 84 quantitative and qualitative research on Corporate Social Management in banking sectors so as to identify 5 areas of emphasis of CSR research in the sectors. These issues are perception toward CSR, drivers, impacts, CS R practices, and CSR reports.